Archive Management at Bpjs Employment Gorontalo City Branch Office - Masayu Anastasya H. Pikoli; Lisda Van Gobel; Andi Yusuf Katili (MultiTech Publisher, 2023)
Archive Management at BPJS Employment Gorontalo City Branch Office. This research uses a descriptive method with a qualitative approach This research was carried out at BPJS Employment Gorontalo Branch Office. Data sources in this study consist of primary data and secondary data. Data collection techniques through observation, structured interviews, and documentation. This data analysis is carried out inductively based on empirical evidence, including: Data Reduction, Data Presentation, and conclusion or verification of Records Management, at the BPJS Employment Branch Office in Gorontalo City which is seen from human resource factors, archive classification, and archival infrastructure facilities are still not optimal in supporting archives at the BPJS Employment Gorontalo City Branch Office. Therefore, the need for additional employees (contract labor), additional facilities and special attention by the head of BPJS in providing facilities and employee needs.